SAFETY OF NEUROAXIAL BLOCKADES AT SURGICAL DELIVERY IN PATIENTS WITH DISSEMINATED SCLEROSIS - E. N. Plakhotina (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
We realized, prospective study, including staging clinicolaboratory and specialized neurological research during 12 months after the operation, to estimate the course of disseminated, sclerosis after Cesarean section at the neuroaxial blockades with use of modern local anesthetics. We observed 17 patients of 26—30 years with disseminated, sclerosis. It is showed, that neuroaxial anesthesia techniques with modern local anesthetics at the operative delivery don't worsen the prognosis of underlying disease.